2017
DOI: 10.1080/01443615.2017.1313823
|View full text |Cite
|
Sign up to set email alerts
|

Maternal distress and the development of hypertensive disorders of pregnancy

Abstract: Despite the implementation of programmes to improve maternal health, maternal and foetal mortality rates still remain high. The presence of maternal distress and its association with the development of pregnancy hypertensive disorders is not well established. The aim of this study was to evaluate the association between maternal distress and the development of hypertensive disorders in pregnancy in a prospective cohort of 321 Mexican women. Symptoms of maternal distressing were evaluated at week 20th of gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…When restricted to studies investigating depression (Avalos, Chen, & Li, 2015; Bandoli & Chambers, 2017; Cripe, Frederick, Qiu, & Williams, 2011; Dayan et al, 2006; De Vera & Bérard, 2012; Goedhart et al, 2010; Henrichs et al, 2010; Hermon, Wainstock, Sheiner, Golan, & Walfisch, 2019; Heun-Johnson et al, 2019; Ibanez et al, 2012; Katon, Russo, Melville, Katon, & Gavin, 2012; Khanghah, Khalesi, & Rad, 2020; Kim et al, 2013; Kurki, Hiilesmaa, Raitasalo, Mattila, & Ylikorkala, 2000; Lutsiv et al, 2015; Mogos et al, 2019; Navaratne, Foo, & Kumar, 2016; Packer, Pilliod, Chatroux, Caughey, & Valent, 2019; Palmsten, Setoguchi, Margulis, Patrick, & Hernández-Díaz, 2012; Qiu, Sanchez, Lam, Garcia, & Williams, 2007; Ruiz et al, 2012; Schmidt et al, 2019; Suri et al, 2007; Venkatesh, Ferguson, Smith, Cantonwine, & McElrath, 2019; Yedid Sion, Harlev, Weintraub, Sergienko, & Sheiner, 2016; Yonkers, Gilstad-Hayden, Forray, & Lipkind, 2017), results indicated an increased risk of HDP (RR = 1.30; 95% CI 1.19–1.43; 26 studies). Analysis of studies on anxiety (Avraham, Tamar, Eyal, & Gali, 2020; Bánhidy, Ács, Puhó, & Czeizel, 2006; Catov, Abatemarco, Markovic, & Roberts, 2010; Chen, Lin, & Lee, 2010; De Vera & Bérard, 2012; Garza-Veloz et al, 2017; Ibanez et al, 2012; Kordi, Vahed, Rezaee, Reza, & Lotfalizadeh, 2017; Pavlov, Steiner, Kessous, Weintraub, & Sheiner, 2014; Ravid et al, 2018) also indicated an increased risk of HDP (RR = 1.49; 95% CI 1.13–21.98; 10 studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When restricted to studies investigating depression (Avalos, Chen, & Li, 2015; Bandoli & Chambers, 2017; Cripe, Frederick, Qiu, & Williams, 2011; Dayan et al, 2006; De Vera & Bérard, 2012; Goedhart et al, 2010; Henrichs et al, 2010; Hermon, Wainstock, Sheiner, Golan, & Walfisch, 2019; Heun-Johnson et al, 2019; Ibanez et al, 2012; Katon, Russo, Melville, Katon, & Gavin, 2012; Khanghah, Khalesi, & Rad, 2020; Kim et al, 2013; Kurki, Hiilesmaa, Raitasalo, Mattila, & Ylikorkala, 2000; Lutsiv et al, 2015; Mogos et al, 2019; Navaratne, Foo, & Kumar, 2016; Packer, Pilliod, Chatroux, Caughey, & Valent, 2019; Palmsten, Setoguchi, Margulis, Patrick, & Hernández-Díaz, 2012; Qiu, Sanchez, Lam, Garcia, & Williams, 2007; Ruiz et al, 2012; Schmidt et al, 2019; Suri et al, 2007; Venkatesh, Ferguson, Smith, Cantonwine, & McElrath, 2019; Yedid Sion, Harlev, Weintraub, Sergienko, & Sheiner, 2016; Yonkers, Gilstad-Hayden, Forray, & Lipkind, 2017), results indicated an increased risk of HDP (RR = 1.30; 95% CI 1.19–1.43; 26 studies). Analysis of studies on anxiety (Avraham, Tamar, Eyal, & Gali, 2020; Bánhidy, Ács, Puhó, & Czeizel, 2006; Catov, Abatemarco, Markovic, & Roberts, 2010; Chen, Lin, & Lee, 2010; De Vera & Bérard, 2012; Garza-Veloz et al, 2017; Ibanez et al, 2012; Kordi, Vahed, Rezaee, Reza, & Lotfalizadeh, 2017; Pavlov, Steiner, Kessous, Weintraub, & Sheiner, 2014; Ravid et al, 2018) also indicated an increased risk of HDP (RR = 1.49; 95% CI 1.13–21.98; 10 studies).…”
Section: Resultsmentioning
confidence: 99%
“…As HDP are diagnosed after 20 weeks' gestation, we next looked at the 17 studies that examined the onset/diagnosis of clinically significant symptoms or a diagnosis of depression mood or an anxiety disorder in pregnancy prior to 20 weeks' gestation (Avalos et al, 2015; Bandoli & Chambers, 2017; Catov et al, 2010; Cripe et al, 2011; De Vera & Bérard, 2012; Garza-Veloz et al, 2017; Goedhart et al, 2010; Henrichs et al, 2010; Ibanez et al, 2012; Kim et al, 2013; Kurki et al, 2000; Lang et al, 2019; Lutsiv et al, 2015; Palmsten et al, 2012; Suri et al, 2007; Suzuki, Shinmura, & Kato, 2015; Winkel et al, 2015) in order to determine if depression or anxiety preceded the diagnosis of HDP. Results of the analysis showed an increased risk of HDP in women who received a diagnosis or had self-reported clinically significant symptoms of depression or an anxiety in pregnancy before 20 weeks' gestation (RR = 1.27; 95% CI 1.07–1.50) 3…”
Section: Resultsmentioning
confidence: 99%
“…Similar to results from our study, prenatal anxiety and depressive disorders have also been shown to significantly increase a person’s risk for a HDP diagnosis, and in some instances result in a shorter gestational period (37). Results from a prospective Mexican cohort showed that anxiety, sleep or social dysfunction, and acute somatic symptoms at 20 weeks of gestation were associated with a higher risk of developing HDP (38). Preexisting depression or anxiety disorder in the one year before conception has been associated with chronic hypertension and preeclampsia during pregnancy (39), and limited research has shown that active-duty women with a PTSD diagnosis before conception were more likely to experience an HDP (40).…”
Section: Discussionmentioning
confidence: 99%
“…A Mexican study found positive association between stress and hypertensive disorders in pregnancy. These authors found that women with more stress symptoms had an increased risk, ranging from 5 to 26 times, to the development of hypertensive disorders in pregnancy (Garza‐Veloz et al, 2017). These results are in line with previous studies which highlighted that prenatal stress is associated with pregnancy‐induced hypertension (Cardwell, 2013).…”
Section: Discussionmentioning
confidence: 99%